Does worksite social capital enhance retention into a worksite weight‐loss programme?. (12th February 2016) - Hill, J. L.; Wilson, K.; Harden, S.; Almeida, F.; Linnan, L.; Estabrooks, P. A.
Summary: Objective: To determine if worksite social capital predicted retention in a worksite‐based weight‐loss programme using structural equation modelling. A secondary aim was to determine if worksite social capital was related to changes in weight at 6 months. Methods: Overweight or obese employees from 28 worksites enrolled in a larger 12‐month worksite weight‐loss trial. Workplace social capital was assessed using an eight‐item scale specific to the workplace. Weight was measured using a HealthSpot tm, and change in weight was computed from weigh‐ins at baseline and 6 months and reported as pounds (lbs) lost. Retention was defined as those employees who completed a weigh‐in at 6 months. Results: Across the trial, N = 1, 790; age = 46.6 ± 11; 73% women; 73% White overweight or obese employees participated. The odds of participant attrition were 1.12 times greater with each unit decrease in social capital score at baseline ( p < 0.05), and while the model testing the direct effect of social capital at baseline on weight loss at 6 months demonstrated acceptable fit, social capital was not a significant predictor of weight loss ( p > 0.05). Conclusions: Increased worksite social capital was predictive of retention in a worksite weight‐loss programme. To maximize return on investments for employee wellness and weight‐loss programmes, employers may benefit from understanding the facets of the 'social' environment such as social capital that may increase the likelihood of sustained participation.